Late diagnosis iniencephaly with spina bifida - Chapman, Dilek Marangoz (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Herein a rare case of iniencephaly combined with spina bifida is reported, which was diagnosed late because the G6P5 mother had not attended hospital for first trimester anomaly scans and alpha-fetoprotein measurement. A woman aged 33 years who was 38 weeks pregnant presented for ante-natal follow-up. Her clinical results were normal but abnormalities including polyhydramnios, retroflexion of the head with absence of neck, acrania, and severe growth retardation were observed in the fetus. The infant was delivered through Cesarean section and died shortly after birth. The results of a gross examination revealed acrania, iniencephaly, spina bifida, and an imperforated anus. Iniencephaly is a rare and fatal neural tube defect characterized by extreme retroflexion of the head and severs distortion of the spine. This case report underlines the importance of first trimester anomaly scans and alpha-fetoprotein measurement.